Multiobjective optimization framework for designing a vehicle suspension system. A comparison of optimization algorithms. (February 2023) - Llopis-Albert, Carlos; Rubio, Francisco; Zeng, Shouzhen
Highlights: A multiobjective optimization framework for designing a vehicle suspension system is developed. We couple several computer-aided design tools (CAD) and computer-aided engineering (CAE) software. A comparison of optimization algorithms is carried out and the Pareto-optimal front obtained. Results show that the use of such approach may significantly improve the design of the suspension system. The optimized objectives improve passengers' comfort, vehicle stability and manoeuvrability, and system fatigue life. Abstract: Recent advances in robotics and digital technologies in the automotive industry, allow the integration of vehicle systems with their virtual twins, thus facilitating their modelling and optimization. As a result, the systems design time and manufacturing costs are substantially reduced, while their performance, safety and fatigue life are expanded. This work presents a multiobjective optimization framework for developing an optimal design of a front double wishbone vehicle suspension system based on a four-bar mechanism. This is carried out by coupling several computer-aided design tools (CAD) and computer-aided engineering (CAE) software. The 3D CAD model of the lower control arm of the suspension system is made using SolidWorks®, the Finite Element Analysis (FEA) of the suspension assembly is modelled using ANSYS® Workbench, while the multibody kinetic and dynamic of the designed suspension system is analysed using MSC ADAMS®. They are embedded in a multidisciplinary optimization design framework (modeFrontier®) with the aim of determining the optimal hardpoint locations of a lower control arm by minimizing the chassis pitch accelerations to improve the passengers' comfort, reducing the volume and mass of the suspension system to increase the vehicle stability and manoeuvrability, while decreasing the maximum stresses to extend the system fatigue life and enhancing safety. The methodology has been successfully applied to several driving scenarios entailing different vehicle dynamics manoeuvres with the aim to find the Pareto optimal front, and to analyse the suspension assembly performance together with the vehicle dynamic behaviour. Results show that the use of such approach may significantly improve the design of the suspension system. Furthermore, a comparison of different optimization strategies and algorithms is performed.